A new life with a new language: Russophone immigrants’ reflections about language learning - Protassova, Ekaterina; Yelenevskaya, Maria (Frontiers in Sociology, 2024)
IntroductionThis research investigates resilience and lived experiences of transnational Russophone families amidst global changes, with a focus on the intricate dynamics of communities spread across borders. The study emphasizes the importance of considering individual migrant experiences in understanding language learning and integration. We explored perceptions of local language proficiency among Russophones; challenges faced by adult Russophones in learning a new language; attitudes and experiences of adults regarding language learning; and strategies Russophone immigrants use to address gaps in the target language.MethodsMethodologically, the research employs ethnographic and thematic analyses, drawing on a diverse array of sources including interviews, social media posts, and personal communications. This approach highlights the necessity of considering both prompted responses and spontaneous discussions to capture authentic opinions on language learning from various perspectives.ResultsThe study underscores the interconnectedness and interdependence within transnational families, illustrating how their lives are shaped by factors that transcend national boundaries. The examination of their diverse experiences reveals their capacity to endure and overcome challenges of integrating into new societies. Russophone migrants’ attitudes toward language learning highlight how learning the host country’s language enhances integration and social mobility, while maintaining the native language preserves cultural heritage, although second-generation immigrants often feel disconnected from their linguistic roots.DiscussionStudies by various authors discuss challenges which immigrants face when adapting to a new linguistic environment. This project emphasizes the impact of language learning on identity and reveals cultural flexibility in attaining social justice in multicultural contexts. These insights suggest that language programs and policies should address both the practical needs of immigrants and the preservation of their cultural identities taking into account their naïve views about language learning.